Visual assessment of antimicrobial medicine packaging and labeling quality in pharmacies of Ho Municipality, Ghana - Emmanuel Orman; Bridget Dzidzinu Ankah; David Oteng; David Mccarthur; Thelma Alalbila Aku; Araba Ata Hutton-Nyameaye; Jonathan Jato; Hayford Odoi; Samuel Owusu Somuah; Issaka Nii Amu Collison-Cofie; Yogini H. Jani; Cornelius Dodoo (PLoS ONE, 2026)
Background Substandard and falsified antimicrobials threaten public health due to their role in resistance development. Pharmacies, as key access points for antimicrobials, can play a crucial role in detecting these products. In this study, a visual assessment tool which incorporates a novel packaging quality index estimate, was developed and used in pharmacies to evaluate antimicrobial packaging and flag suspicious products. Methods A cross-sectional study was conducted in 23 community pharmacies in the Ho Municipality between November 2023 and February 2024. The developed checklist contains indicators on registration compliance, language & medical information, batch information consistency, and product security of the antimicrobials. The tool was validated, and its use on randomly sampled antimicrobials informed the development of the packaging quality index from regression analysis involving weights determined from principal component analysis of the results. Statistical analyses were performed with SPSS (version 26.0) and OriginPro (version 2022). Results The packages and labels of the 275 antimicrobials evaluated were antibacterials (41%), antiprotozoals (28%), antifungals (22%) and antivirals (9%). Most products were of foreign origin (58.5%) and labelled in English (98%). Significant variations were observed in the registration compliance and product security indicators by origin and antimicrobial class ( p < 0.01). Batch information consistency varied significantly across the antimicrobial classes ( p < 0.01), whereas language & medical information quality remained consistent. The packaging quality index scores followed a normal distribution, with majority (95.6%) referred to as moderate quality (Index: 1.81–5.34). High quality packages (2.2%; Index: 5.47–5.53) were mostly observed in antibacterials of local origin (66.7%) whereas the poor-quality packages observed (2.2%; Index: 1.48–1.78) were mostly antibacterials of foreign origin (66.7%). Conclusion This study identified packaging quality issues among the antimicrobials investigated which may suggest potential risk to falsification. Routine antimicrobials packages assessment with developed tools like the packaging quality index could help pick up early signals of substandard and falsified antimicrobials for further regulatory investigations and action.